TECHNIQUES TO INSTRUCT FUTURE EDUCATORS IN THE APPLICATION OF A SYSTEMATIZED PROGRAMMING TASK BASES - Akhmadullaeva , Б.; Rakhimzhanova, Л.; Issabayeva , С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
This paper presents a study on implementing a structured task database to facilitate programming training for students at a pedagogical university. Programming is an intricate field within computer science that necessitates advanced analytical abilities for students in school to comprehend. Therefore, a well-developed approach is necessary for efficient instruction. The hypothesis suggests that incorporating the flipped classroom methodology in training prospective computer science teachers, using a structured set of tasks based on specific criteria, can enhance the effectiveness and productivity of their training in the educational process. The results of the pedagogical experiment demonstrate that implementing the flipped classroom methodology in training future computer science teachers, along with a structured set of tasks, leads to improved teaching effectiveness, student motivation, and engagement in the educational process. Prior to the commencement of the class, students engage in the activity of viewing video lectures and studying the offered content. They then acquire practical skills in a classroom setting during the class itself. Following the session, they proceed to complete assignments. This instructional framework enables the training of prospective educators to effectively apply their knowledge, skills, talents, and professional competencies in their future teaching endeavors.